Mechanical, dielectric and thermal properties of porous boron nitride/silicon oxynitride ceramic composites prepared by pressureless sintering. Issue 11 (1st August 2017) - Sun, Yangshan; Yang, Zhihua; Cai, Delong; Li, Qian; Li, Hailiang; Wang, Shengjin; Jia, Dechang; Zhou, Yu
Abstract: Porous boron nitride/silicon oxynitride (BN/Si2 N2 O) composites were fabricated by pressureless sintering at 1650 °C with Li2 O as sintering aid. The influence of Li2 O and hexagonal boron nitride (h-BN) contents on phase, microstructure, mechanical, dielectric and thermal properties of the resulting porous BN/Si2 N2 O composites was investigated. Increasing Li2 O content facilitated densification and decomposition of Si2 N2 O into Si3 N4 . The apparent porosity of the composites increases with the h-BN content increases and Si2 N2 O grain growth was restrained by the dispersed h-BN particles. The dielectric properties and thermal conductivities (TC) were affected mainly by porosity. Porous BN/Si2 N2 O ceramic composites with 4 mol% Li2 O and 25 mol% BN exhibit both low dielectric constant (3.83) and dielectric loss tangent (0.008) with good mechanical and thermal performance, suggesting possible use as high-temperature structural/functional materials.